Edaravone Dexborneol Treatment Attenuates Neuronal Apoptosis and Improves Neurological Function by Suppressing 4-HNE-Associated Oxidative Stress After Subarachnoid Hemorrhage - Chen, Qian; Cai, Yichen; Zhu, Xiaoyu; Wang, Jing; Gao, Feng; Yang, Mingfeng; Mao, Leilei; Zhang, Zongyong; Sun, Baoliang (Frontiers in Pharmacology, 2022)
EEdaravone dexborneol is a novel neuroprotective drug that comprises edaravone and (+)-borneol in a 4:1 ratio. Phase II and III studies have demonstrated that Chinese patients treated with Edaravone dexborneol within 48 hours of AIS onset have better functional outcomes than those treated with edaravone alone. However, the effect of edaravone Dexborneol on subarachnoid hemorrhage (SAH) has not yet been elucidated. This study aimed to investigate the therapeutic effects of edaravone dexborneol on SAH-induced brain injury and long-term behavioral deficits and to explore the possible mechanisms. The experimental rat SAH model was induced by intraluminal puncture of the left middle cerebral artery (MCA). Edaravone dexborneol or edaravone at a clinical dose was infused into the tail vein for 3 days post-SAH surgery. Behavioral outcomes were assessed by a modified Garcia scoring system, and rotarod, foot-fault, and corner tests. Immunofluorescence, western blot and ELISA methods were used to evaluate the neuronal damage and oxidative stress. Our results showed that a post-SAH therapeutic regimen with edaravone dexborneol helped to improve neurological function up to 21 d after SAH surgery and demonstrated a greater beneficial effect than edaravone alone, accompanied by an obvious inhibition of neuronal apoptosis in the CA1 hippocampus and basal cortex regions. Mechanistically, edaravone dexborneol not only suppressed the lipid peroxidation product malondialdehyde (MDA), but also improved the total antioxidant capability (TAC) 3 days after SAH. Notably, edaravone dexborneol treatment significantly inhibited the expression of another lipid peroxidation product, 4-hydroxynonenal (4-HNE), in the CA1 hippocampus and basal cortex, which are vital participants in the process of neuronal oxidative damage and death after SAH because of their acute cytotoxicity. Together, our results demonstrate that edaravone dexborneol confers neuroprotection and stabilizes long-term behavioral ability after SAH injury, possibly by suppressing 4-HNE associated oxidative stress. These results may help develop new clinical strategies for SAH treatment.